HSPB5 Inhibition by NCI-41356 Reduces Experimental Lung Fibrosis by Blocking TGF-β1 Signaling - Julie Tanguy; Pierre-Marie Boutanquoi; Olivier Burgy; Lucile Dondaine; Guillaume Beltramo; Burhan Uyanik; Carmen Garrido; Philippe Bonniaud; Pierre-Simon Bellaye; Françoise Goirand (MDPI AG, 2023)
Idiopathic pulmonary fibrosis is a chronic, progressive and lethal disease of unknown etiology that ranks among the most frequent interstitial lung diseases. Idiopathic pulmonary fibrosis is characterized by dysregulated healing mechanisms that lead to the accumulation of large amounts of collagen in the lung tissue that disrupts the alveolar architecture. The two currently available treatments, nintedanib and pirfenidone, are only able to slow down the disease without being curative. We demonstrated in the past that HSPB5, a low molecular weight heat shock protein, was involved in the development of fibrosis and therefore was a potential therapeutic target. Here, we have explored whether NCI-41356, a chemical inhibitor of HSPB5, can limit the development of pulmonary fibrosis. In vivo, we used a mouse model in which fibrosis was induced by intratracheal injection of bleomycin. Mice were treated with NaCl or NCI-41356 (six times intravenously or three times intratracheally). Fibrosis was evaluated by collagen quantification, immunofluorescence and TGF-β gene expression. In vitro, we studied the specific role of NCI-41356 on the chaperone function of HSPB5 and the inhibitory properties of NCI-41356 on HSPB5 interaction with its partner SMAD4 during fibrosis. TGF-β1 signaling was evaluated by immunofluorescence and Western Blot in epithelial cells treated with TGF-β1 with or without NCI-41356. In vivo, NCI-41356 reduced the accumulation of collagen, the expression of TGF-β1 and pro-fibrotic markers (PAI-1, α-SMA). In vitro, NCI-41356 decreased the interaction between HSPB5 and SMAD4 and thus modulated the SMAD4 canonical nuclear translocation involved in TGF-β1 signaling, which may explain NCI-41356 anti-fibrotic properties. In this study, we determined that inhibition of HSPB5 by NCI-41356 could limit pulmonary fibrosis in mice by limiting the synthesis of collagen and pro-fibrotic markers. At the molecular level, this outcome may be explained by the effect of NCI-41356 inhibiting HSPB5/SMAD4 interaction, thus modulating SMAD4 and TGF-β1 signaling. Further investigations are needed to determine whether these results can be transposed to humans.